2010
DOI: 10.1103/physrevlett.104.180401
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Temperature in the Approach to Magnetic Order of Ultracold Fermions in an Optical Lattice

Abstract: We perform a quantitative simulation of the repulsive Fermi-Hubbard model using an ultracold gas trapped in an optical lattice. The entropy of the system is determined by comparing accurate measurements of the equilibrium double occupancy with theoretical calculations over a wide range of parameters. We demonstrate the applicability of both high-temperature series and dynamical mean-field theory to obtain quantitative agreement with the experimental data. The reliability of the entropy determination is confirm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(213 citation statements)
references
References 31 publications
7
206
0
Order By: Relevance
“…We plot the temperature as a function of ρ for various values of the total entropy per particle. Recent studies have shown that the entropy per particle (s) for a particular U can be estimated by fitting the doubleoccupancy measurements at different ρ to data from numerical simulations [8]. In Figs.…”
Section: E Trapped Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…We plot the temperature as a function of ρ for various values of the total entropy per particle. Recent studies have shown that the entropy per particle (s) for a particular U can be estimated by fitting the doubleoccupancy measurements at different ρ to data from numerical simulations [8]. In Figs.…”
Section: E Trapped Systemsmentioning
confidence: 99%
“…On the theoretical side, there is an ever-increasing demand for precise numerical results for the relevant parameters of the Hubbard model and for large enough system sizes, which could be used to interpret current experiments and also provide suggestions for future experiments [6][7][8][9][10][11]. For this model, especially for strong interactions, the present computations become particularly challenging as the temperature is lowered below the hopping amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the igh degree of control over the interaction parameters alows for using atomic systems as quantum simulators of eneric theoretical models [2]. Central to these efforts ies the possibility of observing quantum phase transiions (QPT).…”
Section: Introductionmentioning
confidence: 99%
“…Our calculations of the entropy per particle presented above helps us to generate temperature calibration curves which can be used to estimate the temperature of the system during experiments, as has already been done for fermions [32]. In Fig.…”
Section: A Temperature Calibrationmentioning
confidence: 99%